Origin of the synthetic circuits and the Brownian motion in stretchable crystal violet doped and biocompatible composite hydrogels - Ozturk, Muhittin; Coskun, Ramazan; Okutan, Mustafa; Yalcin, Orhan (ELSEVIER, 2018)
Crystal violet dye doped hydrogels as real materials with varying doses have been prepared for smart synthetic circuits in flexible electronic devices by using the polymerization technique. The electric modulus-based Cole Cole diagrams and their adopted to Smith-Chart, frequency evolution of the dielectric properties, and correlation effects in a viscoelastic (Maxwell)system were analyzed by using the impedance spectroscopy at room temperature. The synthetic electric circuits, the Brownian motion, the viscoelastic/relaxation behavior, the fluctuation feature of the concentrations and the total polarization effects are observed for the crystal violet doped biocompatible hydrogels. The observed circuit and Brownian motion in Maxwell system originated from the interaction between dye ions and hydrogels, coulomb interaction between crystal violet dye molecules and oxygen groups, and the ion-migration in the composite hydrogels channels. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Hydrogels; Synthesis; Dielectric properties; Modulus; Viscoelastic properties; DIELECTRIC-PROPERTIES; IONIC LIQUID; GRAPHENE HYDROGELS; ELECTRICAL-CONDUCTIVITY; STRUCTURAL-PROPERTIES; LIVING POLYMERS; CROSS-LINKING; RELAXATION; GELS; SPECTROSCOPY; Chemistry; Physics